Saúde e apoio social na perspectiva do indivíduo idoso - Andrade, Carolina Parente de (2012)
The elderly now occupies 11.3% of the brazilian population and it has afforded the society for being increasingly dealing with issues related to aging. Knowing that the population aging, but not try to understand how this happens does not prepare for this aging society The objective of this research was to investigate the concept of health from the perspective of the elderly. Specifically it sought to analyze: how they perceive their own health, the strategies to keep it and what factors can affect it. It was conducted with 12 individuals from both sexes, aged between 62 and 81 years of middle and upper social classes. After a content analysis can be seen that they answered to an interview consisting of questions related to the purposes of research and its socio-demographic data. It´s possible to be see: the great importance given to health, expanding the traditional concept of this term as absence of disease; they adopt many strategies to keep it;. Concerns about family appeared as the main factors that affect their health. It can be concluded that, in general, they perceived themselves as having good health.